Quantitative Technique to Precisely Fix the Tibia With a Locking Compression Plate at the Preoperatively Planned Correction Angle While Applying High Compression to the Osteotomy Site in Inverted V–Shaped High Tibial Osteotomy - Takuma Kaibara, M.D., Ph.D.; Kazunori Yasuda, M.D., Ph.D.; Eiji Kondo, M.D., Ph.D.; Koji Yabuuchi, M.D.; Jun Onodera, M.D., Ph.D.; Norimasa Iwasaki, M.D., Ph.D.; Tomonori Yagi, M.D., Ph.D. (Arthroscopy Techniques)
In high tibial osteotomy (HTO) fixed with a locking compression plate (LCP), overcorrection or under-correction of knee alignment frequently occurs because the LCP applies not only proximal displacement but also valgus rotation to the distal tibia. We have developed a quantitative technique to precisely fix the tibia with the LCP at the preoperatively planned correction angle in inverted V–shaped HTO. Preoperatively, simulation of the HTO using the LCP is performed with a radiograph, and the distance of the most proximal locking screw from the articular surface is measured. During surgery, a marker wire is precisely inserted into the proximal tibia at the preoperatively planned position of the most proximal locking screw. By inserting the first screw along this marker wire, the LCP is precisely installed on the proximal tibia at the planned position. Then, a compression screw is inserted into the distal tibia through the LCP. This screw pulls the distal tibia toward the distal part of the LCP while applying proximal displacement and valgus rotation. Thus, the tibia is precisely fixed at the planned correction angle.